Gambaran Penggunaan Obat Antidiare di 3 Puskesmas Kabupaten Barito Selatan: Description of The Use of Antidiarrheal in 3 South Barito District Health Centers - Nurul Chusna; Evi Mulyani; Ahmad Asmadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Diarrhea is a disease characterized by an increase in the frequency of defecation more than three times a day accompanied by changes in the shape and consistency of feces of patients. Bacterial, viral or parasitic infections can cause diarrhea. This study aimed to determine the profile of the use of antidiarrheal drugs for one semester in 3 South Barito District Health Centers namely Bangkuang Health Center, Sababilah Health Center, and Buntok Health Center. The results showed that there were differences in the use of drugs in each Health Center. Based on the type of drug that is most widely used, namely for the Bangkuang Health Center was Zink (1300 prescription), for Sababilah Health Center was Metronidazole (1350 prescription), and for Buntok Health Center was Cotrimoxazole (4650 prescriptions). Based on the age of patients aged 18-60 years for Bangkuang Health Center as many as 120 people, 279 people for Sababilah Health Center, and 315 people for Buntok Health Center. Based on male and female sex, for Bangkuang Health Center were 98 males and 167 females, for Sababilah Health Center were 233 males and 258 females, and for Buntok Health Center were 298 males and 398 females. Further research needed for a long time regarding the use of antidiarrheal drugs in other Health Centers.